Beyond quality and quantity: Representing empirical structures by embedded typologies - Borgstede, Matthias; Rau, Caroline (Frontiers in Education, 2023)
In this article, we propose a new approach to the problem of integration in mixed methods research that builds on a representational understanding of empirical science. From this perspective, qualitative and quantitative modeling strategies constitute two different ways to represent empirical structures. Whereas qualitative representations focus on the construction of types from cases, quantitative representations focus on the construction of dimensions from variables. We argue that types and dimensions should be integrated within a joint representation of the data that equally acknowledges qualitative and quantitative aspects. We outline how the proposed representational framework can be used to embed qualitative types in quantitative dimensions using an empirical study on teachers’ epistemological beliefs.